TOPSIS multiobjective optimization of powder metallurgy process parameters: Al-NiTi-SiC smart composites. (2021) - Purusothaman, M.; Rajesh, S.; Chokkalingam, R.
Highlights: This article discusses the importance of powder metallurgy process parameter to fabricate smart composites. The shape memory material is used as reinforcement materials to study the mechanical properties of the smart composites. The effect of augmentation of nano SiC on smart composites is studied and presented. TOPSIS Multiobjective Optimization is used to optimize the powder metallurgy process parameters. Abstract: The proposed work is aiming to present the influence of powder metallurgy process parameter such as applied load, sintering temperature and time on mechanical properties of the smart composite materials. Aluminium, 5% NiTi, and 1% nano SiC are used as matrix and reinforcement materials. Powder metallurgy method is employed to fabricate the essential number of smart composites. The essential number of composites is fabricated with varying loads, sintering temperature and sintering time. Applied load is selected in the range of 200 to 300 kN with the interval of 50 kN and sintering temperature varied between 500 and 600 °C with the interval of 50 °C. Sintering time is also varied between 30 and 60 min. with the interval of 15 °C. According to ASTM standard, the properties of the composites such as compression strength, hardness, etc. are measured and it is found that augmentation of reinforcements increased the compression strength and similar kind of observation is also made while increasing the sintering temperature. The result of TOPSIS multi-objective optimization formulated to identify the optimal grouping of powder metallurgy process parameter. It is established form the testing, the most influencing process parameters are set at A1, B2 and C2 .